Isolation and differentiation of vibrio species from seafood and molecular characterisation of vibrio parahaemolyticus / Mohammadjavad Paydar - Paydar, Mohammadjavad (2013)
Vibrio species are significant causes of gastroenteritis in humans associated with consumption of raw or under-cooked seafood. Pathogenic vibrios are common causes of seafood-borne illness in Southeast Asian countries including Malaysia, where the temperature is optimal for their growth. The objectives of this study were to investigate the prevalence of Vibrio spp. in raw seafood using conventional and molecular methods; to compare these methods based on their sensitivity and discriminatory power; and to analyse pathogenicity and genetic variability of V. parahaemolyticus isolates. One-hundred and fifty seafood samples, including fish, shrimps, prawns, cockles, oysters, clams and squids, were collected from retail stores and hypermarkets in Kuala Lumpur, Petaling Jaya and Seri Kembangan. Colony appearance on CHROMagarTM Vibrio and thiosulfate-citrate-bile salts-sucrose (TCBS), followed by conventional biochemical tests including oxidase, Triple Sugar Iron (TSI), Sulfur reduction – Indole – Motility (SIM), Methyl Red (MR) and Voges-Proskauer (VP), and salt tolerance tests were used for preliminary identification of Vibrio species.API 20E test strip, was applied for biochemical confirmation of vibrios. A multiplex polymerase chain reaction (PCR) targeting gyrB gene for detection of Vibrio spp., and pntA genes for V. cholerae, V. parahaemolyticus and V. vulnificus was further evaluated on spiked fish, shrimp and oyster, respectively. Sensitivity of the multiplex PCR on spiked seafood was 2.0x103 CFU ml-1 for V. cholerae and V. parahaemolyticus, and 9.0x103 CFU mL-1 for V. vulnificus. The multiplex PCR indicated 100% accuracy and 100% specificity, hence it was used for confirmation of the isolates. Based on the multiplex PCR results, 63% (93/150) of the seafood samples, purchased from the retail stores, harboured Vibrio spp., where the prevalence of V. cholerae, V. parahaemolyticus and V. vulnificus was 5.3% (8/150), 29% (43/150) and 8% (12/150), respectively. PCR determination of the iv virulence genes in V. parahaemolyticus isolates showed that all of the isolates tested (n =50) contained toxR gene, while 4% (2/5) and 12% (6/50) contained thermostable direct hemolysin (tdh) gene and thermostable direct hemolysin-related (trh) gene, respectively. Repetitive Extragenic Palindromic PCR (REP-PCR) was performed to genetically characterize the V. parahaemolyticus isolates. Forty-one REP profiles were observed and V. parahaemolyticus isolates were categorized into 10 distinct clusters at 80% similarity. In summary, detection of Vibrio spp. was done more efficiently by CHROMagarTM Vibrio rather than TCBS. Comparison of the results of biochemical tests with multiplex PCR indicated that API 20E had higher discriminatory power (83%) to differentiate V. cholerae, V. parahaemolyticus and V. vulnificus, compared to the conventional biochemical tests (56%). The gyrB/pntA genes-based multiplex PCR was confirmed as an accurate and efficient screening tool for detection of Vibrio spp. Virulent V. parahaemolyticus isolates were isolated from seafood and it implies a potential risk to consumers if such seafoods were consumed uncooked. High genetic diversity of the V. parahaemolyticus isolates was shown by REP-PCR and it was able to distinguish the isolates with different virulotypes.